SOCIAL CAPITAL CONTRIBUTION IN THE CONTINUOUS STRATEGY OF JENGKOL MANUFACTURERS IN THE COVID-19 PANDEMIC - Rusmaniah Rusmaniah; Dedy Ari Nugroho (Universitas Lambung Mangkurat, 2022)
The COVID-19 pandemic has an impact on the sector in Indonesia. One of them occurred in jengkol producers in Pingaran village, Banjar Regency, which decreased by 50%. This study aims to describe the social capital that exists in the lives of jengkol producers and the contribution of social capital in the jengkol business continuity strategy during the covid-19 pandemic. That approach is qualitative. Collecting data through in-depth interviews, observation, and documentation. Data analysis went through the reduction, presentation, and conclusion stages and was finally verified. The benefit of this research is that it can determine the contribution of social capital and strategies in maintaining a business amid the covid-19 pandemic. The results of the study explain the elements of social capital that are formed, namely networks, norms, and trust. The most dominant element of social capital in the jengkol business is the network element. The strategies carried out by jengkol producers in business continuity include good relations between fellow jengkol traders, using secret ingredients, expanding marketing networks, and using government funding as a solution for capital continuity.